Combating building illegality in Hong Kong: A policy Delphi study. (October 2015) - Yau, Yung; Chiu, Shuk Man
Abstract: Building illegality, which usually takes the form of unauthorised building works (UBWs), has posed serious threats to the safety of the community in many cities. In spite of the plenteous literature on this topic, studies related to the development of policy combating UBWs are relatively rare. To straddle this research gap, a policy Delphi study is carried out with an expert panel to identify and prioritise policy options for combating UBWs in Hong Kong. The policy Delphi method, being a multistage process, is adopted because it allows a systematic approach to obtain, exchange and develop informed options on a particular policy issue. Hong Kong is a good laboratory for the study of UBW-related policy, because there are over one million UBWs of different types throughout the territory. More importantly, the issues of UBW have triggered various political crises and sagas in Hong Kong. The results of a three-round policy Delphi survey suggest that imposing heavier punishments against non-conforming owners is the top priority option. Options like simplification of the building approval process and expedited implementation of mandatory building inspections are poorly received. These findings have far-reaching implications for the formulation of government policies regarding building safety in Hong Kong. Highlights: Building illegality has not received much attention in the field of urban studies. Measures to combat unauthorised building works in Hong Kong were explored. Policy options were identified and prioritised using policy Delphi. Imposing heavier punishments was regarded as the top priority option.